The Potential of Android Learning Media Based on Visual Representation to Improve Students' Representation and Systems Thinking Skills: A Review From a Student Teacher's Perspective - Ilmiyatni, Fatynia; Setyarini, Marina; Lengkana, Dewi (International Journal of Education, Culture, and Society, 2025)
Despite growing recognition of the importance of representation and systems thinking skills in science education, limited research has explored the use of Android-based learning media grounded in visual representations to support these competencies. This study aims to characterize Android learning media designed with visual representations and examine perceptions of its effectiveness in enhancing students’ representational and systems thinking skills. Employing an explanatory sequential mixed-methods design, the research involved 44 science teachers and 244 junior high school students across Lampung Province, Indonesia. Quantitative data were collected through structured questionnaires, followed by qualitative interviews to elaborate on the initial findings. Data analysis employed appropriate statistical and thematic techniques. The results indicate that both teachers and students hold favorable perceptions of visual representation-based Android learning media, recognizing its potential to support student understanding and cognitive development in science. The study concludes that such media are perceived as effective tools for improving students' abilities in scientific representation and systems thinking. Theoretically, the study contributes to the growing body of literature on educational technology and visual learning tools in science education. Practically, it encourages educators and curriculum developers to integrate these tools to address gaps in students' representational competence and implicit system thinking. Future research is recommended to examine the long-term impacts and effective integration strategies of visual representation-based digital media in diverse learning environments.